PERANCANGAN SISTEM INFORMASI PENJUALAN SOFT DRINK SERIES BERBASIS WEB MENGGUNAKAN METODE AGILE PADA PT. CITA RASA MEDIA - Basir, Basir; Pamungkas, Bayu Aji; Wahyudi, Supri; Haryono, Wasis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Pamulang, 2023)
The current sales process is still carried out by meeting directly with sellers and customers so it is still less effective to have a role in the business field. Along with the development of technology, it can be used to increase promotion and processing existing data to be used as information. The development of information technology which is accompanied by the development of the internet supports each other so as to give birth to the concept of internetbased Information Technology whose development is increasingly widespread and is increasingly being applied to the company's business in various fields in order to achieve the goals desired by the company. Agile method is one of the most effective and agile software development methods. Agile method software which is divided into six stages, namely Planning, Implementation, Testing, Documentation, Deployment, and Maintenance. The purpose of this research is to be able to solve the problem of how to design a website-based sales information system that is able to facilitate the dissemination of product information, facilitate sales without having to come to the location, The conclusion is to make it easier for the owner to make payments without having to come to the store. The process is very